Advanced modulation and detection techniques for indoor visible light communication systems - Chen, Chen (2017)
Illuminating light-emitting diodes (LEDs) enabled visible light communication (VLC) has attracted ever-increasing attention in recent years, due to the rapid development of solid-state lighting technology. The LEDs in general VLC systems play a dual role of providing simultaneous illumination and high-speed wireless data communication in typical indoor environments. Compared with traditional radio-frequency (RF) systems, VLC has many inherent advantages including license-free spectrum, high data rate, cost-effective front-ends, high security, electro-magnetic interference (EMI)-free operation, etc. By exploiting high-speed, bidirectional and fully networked VLC in indoor environments, light-fidelity (Li-Fi) can be realized which is envisioned as a promising complementary technology to the widely used wireless-fidelity (Wi-Fi). Nevertheless, the development and deployment of high-speed and large-coverage indoor VLC systems face many critical issues, such as the small 3-dB modulation bandwidth of commercially available off-the-shelf white LEDs, the limited coverage of each LED access point (i.e., optical attocell) due to the constraints of both illumination and communication, the inter-cell interference (ICI) in indoor multi-cell VLC systems, and the seamless integration of VLC with the last-mile optical access networks for hybrid wired and wireless indoor optical access. The main objectives of this thesis are to address the above issues, and propose and develop advanced transmission, modulation and detection techniques to improve the performance of VLC systems.